2022
DOI: 10.1111/twec.13320
|View full text |Cite
|
Sign up to set email alerts
|

Global value chains and female employment: The evidence from Vietnam

Abstract: What is the relationship between female employment and global value chains (GVCs) in developing countries? Motivated by the rise of offshoring into Vietnam, we study Vietnam's small and medium enterprises (SMEs) from 2011 to 2015. The empirical findings suggest a positive association between global value chains and the female share of total workforce, unskilled workforce and production workforce; while GVCs are negatively associated with the female share of skilled workforce and non‐production workforce. Intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…A related issue concerns the global value chain (GVC). Studies have documented a higher presence of female than male workers in GVCs than elsewhere (Pham & Jinjarak, 2022;Rocha & Winkler, 2019;World Bank, 2020b). One reason for this could be that GVCs in developing countries are typically involved in tasks that are routine and low-skilled, requiring dexterity of work and nimble fingers (the "task trade" theory), in which females have a comparative advantage over males.…”
Section: Baseline Controlsmentioning
confidence: 99%
“…A related issue concerns the global value chain (GVC). Studies have documented a higher presence of female than male workers in GVCs than elsewhere (Pham & Jinjarak, 2022;Rocha & Winkler, 2019;World Bank, 2020b). One reason for this could be that GVCs in developing countries are typically involved in tasks that are routine and low-skilled, requiring dexterity of work and nimble fingers (the "task trade" theory), in which females have a comparative advantage over males.…”
Section: Baseline Controlsmentioning
confidence: 99%
“…Existing studies have shown that trade can improve gender equality by increasing competition between firms and reducing gender-based discrimination (Black and Brainerd, 2004;Ederington et al, 2009;Juhn et al, 2013;Aguayo-Tellez et al, 2014), as well as by encouraging firms to undertake technological upgrading (Juhn et al, 2014) that favours female workers with comparative advantage in brain-based work. Pham and Jinjarak (2023) suggests that integration in global value chains is correlated with higher female employment across small and medium firms in Vietnam, but that this is driven by unskilled workers.…”
Section: Introductionmentioning
confidence: 99%